Pengawasan Badan Permusyawaratan Desa Dalam Penggunaan Dana Desa Di Desa Eemokolo Kabupaten Bombana - Jamsen, Tri Angraini; Razak, Rosdianti; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out the Supervision of the Village Consultative Agency (BPD) in the Use of Village Funds in Eemokolo Village, Bombana Regency. This study used a qualitative research that aimed to determine the supervision of BPD based on the problems discussed, namely the problems that occured in the research location. Informants in this study amounted to 5 people, data collection by interview, observation and documentation. Data analysis through data reduction, data presentation and conclusion making, while the validity of the data using triangulation of sources, techniques and time. The results showed that the Eemokolo Village BPD in carrying out its supervisory function was not maximal. The Eemokolo Village BPD's functions and duties were still at the planning stage, such as accommodating the aspirations of residents regarding the management of the Village Fund, while the use and supervision of the budget was still very weak and tended to be uninvolved. The obstacles for BDP in carrying out the function of overseeing human  resources were still low. Lack of cooperation between village governments.  The supervision was not optimal.Keywords: Supervision, Village Consultative Agency, Village Fund.